An assessment of the niche centroid hypothesis: Pteropus lylei (Chiroptera). Issue 5 (26th May 2020) - Chaiyes, Aingorn; Escobar, Luis E.; Willcox, Emma V.; Duengkae, Prateep; Suksavate, Warong; Watcharaanantapong, Pattarawan; Pongpattananurak, Nantachai; Wacharapluesadee, Supaporn; Hemachudha, Thiravat
Abstract: Recent ecological theories propose that species reach their highest abundance and genetic diversity in the center of their ecological niche and decline toward the edges. We assessed whether Lyle's flying fox, Pteropus lylei, abundance and genetic diversity were correlated with niche centroid distance using an ecological niche model as a proxy for fundamental niche ( N F ). Alternatively, we assessed whether P. lylei abundance and genetic diversity were correlated with fine‐scale environmental factors as a proxy of the species' realized niche ( N R ). We examined relationships between abundance and environmental factors at coarse and fine scales as proxies of N F and N R, respectively. For coarse scale, ecological niche of P. lylei was modeled using all available occurrence records in Thailand, Cambodia, and Vietnam, coupled with climatic data. We conducted field measurements of P. lylei abundance and used genetic structure data across a large portion of the species' range. We measured Euclidean distances between abundance and genetic data and the niche centroid in environmental dimensions. Spearman's correlation was estimated between abundance and genetic diversity vs. distance to the niche centroid. Complementarily, for the fine‐scale test, we measured multiple regression models between abundance and genetic diversity versus the normalized difference vegetation index (NDVI), local temperature, percent area of waterbodies, human density, and number of Buddhist temples. We failed to detect relationships between abundance and genetic diversity with the distance to the niche centroid in the coarse‐scale model. When using the fine‐scale, landscape‐level data, we found negative correlation between genetic diversity and number of temples. The data available were unable to support niche centroid hypothesis for the current distribution and abundances of P. lylei . We note that our failure to find an association does not support nor reject the niche centroid hypothesis. Instead, our capacity to test the niche centroid hypothesis may be limited by our ability to use empirical data to accurately reconstruct N F from field observations only. Future research may require physiology‐based experimental approaches to explore relationships between species abundances and the niche structure.